Prophet in educational leadership professionalism critical study in the quran - Suherman, Eman; Zakariya, Aulif Angga; Putri A.S, Dewi Fatimah; Hanif, M. Nashirudin (Universitas Ahmad Dahlan, 2024)
The story of the prophet Yusuf is unique because it tells the entire story of his life. The story of the life of the prophet Yusuf is told in sufficient detail in one letter in the Qur'an. This research is about the professionalism of the prophet Yusuf in his leadership. This study discusses how the characteristics and traits of the prophet Yusuf with regard to leadership can be applied in education. To help fund this research and gain a better understanding, this research begins by compiling the interpretations of classical and contemporary scholars. This study's findings can be concluded that the prophet has 4 professional characteristics, namely Amin which means trustworthy, Makin which means high position, Hafidz which means able to maintain and alim which means having knowledge. As well as characteristics in leadership, including Professional leaders, honest and exemplary, capable, high intelligence, wise, fair, thorough, trustworthy and consistent.